Microstructure and mechanical properties of superelastic NiTi fiber reinforced NiTi/(Al3Ti+Al3Ni) metal-intermetallic laminated (SFR-MIL) composites. (2nd June 2021) - Kang, Fuwei; Zhang, Ximeng; Zhang, Fahong; Wang, Enhao; Cao, Yang; Jiang, Wei; Wang, Liping; Han, Yuqiang; Lin, Chunfa
Abstract: In this work, a novel superelastic NiTi fiber reinforced NiTi/(Al3 Ti+Al3 Ni) metal-intermetallic laminated (SFR-MIL) composites was fabricated via vacuum hot pressing method. In order to accurately determine the reaction products of the fabrication process, the microstructure and phase constituents were analyzed and determined using scanning electron microscopy (SEM), energy dispersive spectroscope (EDS) and x-ray diffraction (XRD). Results showed that Al3 Ti and Al3 Ni were formed during fabrication process. In addition, the quasi-static tensile testing results indicated the average UTS and failure strain of SFR-MIL composite are 377.0 MPa and 15.4%, respectively. The compressive tests of SFR-MIL composites manifested that the average peak compressive strength of this class of materials with load perpendicular to layers is 1114.3 MPa, equivalent to or higher than that of some other laminated composites. Then, the fracture mechanisms are discussed, and the results showed that the reaction band is the possible crack initiation due to the stress concentration, and the major fracture mechanisms are intergranular and transgranular fracture modes.